2015
DOI: 10.1111/mcn.12022
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for lipid‐based nutrient supplements for young children in four urban sites of Ethiopia

Abstract: Malnutrition in children under 5 years of age is pervasive in Ethiopia across all wealth quintiles. The objective of this study was to determine the willingness to pay (WTP) for a week's supply of Nutributter® (a lipid-based nutrient supplement, or LNS) through typical urban Ethiopian retail channels. In February, 2012, 128 respondents from 108 households with 6-24-month-old children had the opportunity to sample Nutributter® for 2 days in their homes as a complementary food. Respondents were asked directly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 13 publications
(17 reference statements)
2
31
1
Order By: Relevance
“…An experimental auction in Burkina Faso revealed an average WTP for SQ‐LNS‐Child of $0.85 for a week's supply (or $0.12/day's supply; Lybbert et al, ). In another study, Segrè et al () elicited WTP for Nutributter®, an LNS product for children, from respondents in urban Ethiopia. That study found that average WTP for a week's supply of Nutributter® based on an experimental auction was approximately $0.80 (or $0.11/day's supply), and average stated WTP was over twice that amount.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental auction in Burkina Faso revealed an average WTP for SQ‐LNS‐Child of $0.85 for a week's supply (or $0.12/day's supply; Lybbert et al, ). In another study, Segrè et al () elicited WTP for Nutributter®, an LNS product for children, from respondents in urban Ethiopia. That study found that average WTP for a week's supply of Nutributter® based on an experimental auction was approximately $0.80 (or $0.11/day's supply), and average stated WTP was over twice that amount.…”
Section: Discussionmentioning
confidence: 99%
“…Several research activities have been undertaken to build an understanding of SQ‐LNS demand, including stated willingness to pay (WTP) in Niger (Tripp et al, ), stated WTP and a short‐term market simulation in Ethiopia (Segrè et al, ), an experimental auction in Ghana (Adams, Lybbert, Vosti, & Ayifah, ), and an experimental auction followed by a market trial in Burkina Faso (Lybbert et al, ). We assessed stated WTP for SQ‐LNS alongside randomized controlled trials in Ghana (DYAD‐G trial) and Malawi (DYAD‐M trial) undertaken by the International Lipid‐Based Nutrient Supplements (iLiNS) Project (http://ilins.org/).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that while most consumers were interested to buy the product and 25% would be willing to pay an unsubsidized price, consumers are not yet used to buying packaged foods for this target group, and total market size would be limited (Segrè et al . ).…”
Section: Access and Distribution Under (Semi) Real‐life Circumstancesmentioning
confidence: 97%
“…With need likely outstripping philanthropic potential, there is interest in exploring commercial sales. A study of Ethiopian households found some willingness to pay for a week's supply of SQ-LNS among nearly all surveyed urban households, with a quarter willing to pay a projected unsubsidized commercial price (Segrè et al, 2012).…”
Section: Small Quantity Lipid-based Nutrient Supplementsmentioning
confidence: 99%